Epithelial-mesenchymal crosstalk: the scriptwriter of craniofacial morphogenesis - Lu, Junjie; Peng, Bo; Wang, Wenyi; Zou, Yi (Frontiers in Cell and Developmental Biology, 2024)
Epithelial-mesenchymal interactions (EMI) are fundamental mechanisms in regulating development and organogenesis. Here we summarized the signaling mechanisms involved in EMI in the major developmental events during craniofacial morphogenesis, including neural crest cell induction, facial primordial growth as well as fusion processes. Regional specificity/polarity are demonstrated in the expression of most signaling molecules that usually act in a mutually synergistic/antagonistic manner. The underlying mechanisms of pathogenesis due to disrupted EMI was also discussed in this review.